Answer:
-76
Step-by-step explanation:
f(x) = x^2– 7. and g(x) = 5 – x^2 ,then g(f(-4)) =
-76
Answer:
The answer is soooo simple
Step-by-step explanation:
its c
Answer:
47
Step-by-step explanation:
The number that should go after 23 is 47.
The pattern seems to be (n * 2) + 1, where n is the value of the previous number.
We start with the number 5:
5
(5 * 2) + 1 = 11
11
(11 * 2) + 1 = 23
23
(23 * 2) + 1 = 47
47
... and so on
The pattern should continue as follows.
Hope this helps!
Answer:
Step-by-step explanation:
Remember all the angles will equal 360 degrees, so add all the other angles together and subtract 360 from the sum of the other three angles for number 5.
5. x = 59 Degrees
6. x = 114 Degrees